2016
DOI: 10.1111/pace.12951
|View full text |Cite
|
Sign up to set email alerts
|

Provider Response to QTc Prolongation on Standard 12‐Lead EKG: Do We Notice or Do We Care?

Abstract: Patients with prolonged QTc on EKG were more likely to be inpatients than outpatients. Inpatients were more likely to be receiving multiple types and classes of QTc prolonging medications. In the vast majority of cases, providers did not address the prolonged QTc and only rarely initiated remedial actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Reports have also been published evaluating the effectiveness of the suggested good clinical practice 9 11 . Regrettably, it has been reported that while the introduction of guidelines and monitoring schemes increases the awareness of the proarrhythmic potentials, therapeutic implications of prolonged QTc interval, such as therapy changes and/or more intensive monitoring, are not necessarily systematically implemented 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Reports have also been published evaluating the effectiveness of the suggested good clinical practice 9 11 . Regrettably, it has been reported that while the introduction of guidelines and monitoring schemes increases the awareness of the proarrhythmic potentials, therapeutic implications of prolonged QTc interval, such as therapy changes and/or more intensive monitoring, are not necessarily systematically implemented 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These lead to the conclusion that the monitoring schemes result in an increase in the knowledge and awareness of the drug‐induced QTc prolongation with consequent proarrhythmic risk among the clinical community. At the same time, however, the available literature also suggests that in terms of clinical implications, for example, therapy changes in susceptible patients, the ECG monitoring schemes are frequently not particularly successful (Good, Riad, Good, & Shalaby, ).…”
Section: Introductionmentioning
confidence: 99%